Triplet Pregnancy with Partial Hydatidiform Mole Coexisting with Two Fetuses after Ovulation Induction and Intrauterine Insemination - Mehmet Serdar Kütük; Mehmet Dolanbay; Hilal Akalın; Mahmut Tuncay Özgün; Turhan Öktem; Munis Dündar; Ercan Aygen (Gynecology Obstetrics & Reproductive Medicine, 2015)
Partial hydatidiform mole with dichorionic twin fetuses is extremely rare condition, and only three cases have been reported before. Twenty- five years old primigravida having a trizygotic triplet pregnancy that has been conceived by ovulation induction and intrauterine insemination was referred to our department for threatened abortion. The fetus B with molar placenta has been selectively terminated at 11th weeks and the pregnancy was complicated with preeclampsia, hyperthyroidism, and culminated in spontaneous abortion at 20th weeks. After the abortion, the pathologic evaluation suggested partial mole, and genetic evaluation confirmed the diagnosis. The postpartum course complicated with persistent trophoblastic disease that well responded to four course of methotrexate therapy. The optimal management of partial hydatidiform mole coexistent with two fetuses is currently uncertain. The choice of continuing the pregnancy must be individualized, depending on the patient condition. These patients should be carefully followed after the pregnancy for persistent trophoblastic disease.